2008
DOI: 10.1007/s00531-008-0376-2
|View full text |Cite
|
Sign up to set email alerts
|

Overpressure within upper continental slope sediments from CPTU data, Gulf of Lion, NW Mediterranean Sea

Abstract: Data from in situ piezocone tests (CPTU) and laboratory analyses are utilized for the interpretation of the stress history of Quaternary sedimentary sequences in the upper continental slope of the Gulf of Lion, northwestern Mediterranean Sea. A CPTU based preconsolidation pressure profile referenced to the current effective stress indicates that the deposit is underconsolidated from 12 meters below the seafloor (mbsf) down to at least 150 mbsf. Excess pore pressure below 12 mbsf is further supported by results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Both methods lead to consistent results with the presence of high excess pore pressure in the superficial (< 10 m) sediments. These results confirm what was already observed by Lafuerza et al () who calculated an excess pore pressure profile from in situ piezocone measurements. Lafuerza et al () suggested that the origin of this superficial excess pore pressure and the presence of pockmark fields in the area (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Both methods lead to consistent results with the presence of high excess pore pressure in the superficial (< 10 m) sediments. These results confirm what was already observed by Lafuerza et al () who calculated an excess pore pressure profile from in situ piezocone measurements. Lafuerza et al () suggested that the origin of this superficial excess pore pressure and the presence of pockmark fields in the area (Fig.…”
Section: Resultssupporting
confidence: 92%
“…These results confirm what was already observed by Lafuerza et al () who calculated an excess pore pressure profile from in situ piezocone measurements. Lafuerza et al () suggested that the origin of this superficial excess pore pressure and the presence of pockmark fields in the area (Fig. ) is a combination of the accumulation of free gas in deep permeable sediment layers and the gas exsolution processes related to sea level variations.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, Lafuerza et al . [] and Riboulot et al . [] have proposed that relative sea level falls decrease hydrostatic pressure and thus increase gas volume in the fluid reservoir, with the formation of gas bubbles subsequently inducing pockmark formation.…”
Section: Introductionmentioning
confidence: 99%
“…An additional factor might be the lowering of the storm-wave base (and related storm-triggered mass wasting), and possibly the exsolution of free gas contained in organic-rich clinoforms of the shelf-edge deltas. This latter process has been demonstrated to be an important factor in the formation of pockmarks situated along the Bourcart/Herault interfluve (Lafuerza et al, 2009;Riboulot et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 94%